Perceived Neighborhood Safety and Active Transportation in Adults from Eight Latin American Countries - Farias-Valenzuela, C (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Neighborhood built environment is associated with domain-specific physical activity. However, few studies with representative samples have examined the association between perceived neighborhood safety indicators and domain-specific active transportation in Latin America. This study aimed to examine the associations of perceived neighborhood safety with domain-specific active transportation in adults from eight Latin American countries. Data were obtained from the Latin American Study of Nutrition and Health (n = 8547, aged 18–65). Active transportation (walking and cycling) was assessed using the long form of the International Physical Activity Questionnaire. Specifically, traffic density and speed as well as street lightening, visibility of residents regarding pedestrians and bicyclists, traffic lights and crosswalks, safety of public spaces during the day and at night, crime rate during the day and at night were used to evaluate perceived neighborhood safety. Slow traffic speeds, unsafe public spaces during the day, and crime during the day were associated with ≥10 min/week vs. <10 min/week of walking. Furthermore, drivers exceeding the speed limit and crime rate during the day were associated with reporting ≥10 min/week vs. <10 min/week of cycling. These results indicate a stronger association of the perceived neighborhood safety with walking compared to cycling. © 2022 by the authors.